WRITING RELIGIOUS HISTORY AS A BELIEVER. - Butler, Anthea (Fides et historia, 2011)
The author reflects on the writing of religious history by Christian believers. Her article responds to the essays "Mormon History Inside Out" by Richard Lyman Bushman, "Historians’ Metaphysical Beliefs and the Writing of Confessional Histories" by Brad S. Gregory, and "Coming to Terms as a Christian Historian with F. H. Bradley" by Mark A. Noll. Particular focus is given to Christian historians' roles in studying the negative impacts of Christian beliefs, communities, and individuals on marginalized groups such as women, colonial subjects, and African-American slaves. Other topics include Enlightenment methodologies of history, religious historians' reputations within the academy, and themes of persecution in Christian historians' writings.